Reduplication in Suwawa Language (International Journal of Multidisciplinary Research and Explorer, 2020)
This study aims at describing the forms of reduplication in the Suwawa Language. Data in this study were gathered from native speakers of the Suwawa language who lived in Suwawa, Bone Bolango Regency, Gorontalo Province. Data were collected through observation, interview, and note-taking techniques. The collected data were then analyzed qualitatively by following the stages of data analysis by Miles, Huberman, & Saldana (2014), consisting of data condensation, data display, and conclusion drawing or data verification. Based on the results of data analysis, the researchers found five forms of reduplication in the Suwawa language: (1) complete reduplication, which can be divided into (a) complete reduplication of basic words and (b) complete reduplication with affixes, (2) reduplication with affixes, (3) reduplication with sound changing, (4) partial reduplication, which can be divided into (a) partial reduplication of one syllable and (b) partial reduplication of two syllables, and (5) pseudo reduplication.